Pengembangan Bahan Ajar Pendidikan Kependudukan dan Lingkungan Hidup (PKLH) Berbasis Karakter Melalui Model Pmbelajaran Quantum Teaching and Learning di STKIP Nasional Padang Pariaman - Sepni Wita; Wage Ummami (Universitas Batanghari Jambi, 2021)
The background of this research is the lack of meaningful learning pklh so that students are less able to take the meaning of learning so that the values of character can not be instilled in the individual of each student. The purpose of this research is to develop character-based teaching materials through a valid, practical, and effective QTL learning model. This type of research is development research using addie development model (Analysis, Design, Development, Implementation, and Evaluation). The sample of this study is students of economic education courses. Data collection techniques by conducting observations and tests. The data is analyzed using descriptive statistical techniques. The results showed that character-based PKLH teaching materials using the QTL model can develop student character, with the student character category in good condition. The level of validity, practicality, and effectiveness that are in the category is very valid, very practical, and very effective. This development research has produced products in the form of character-based teaching materials. The implications of character-based teaching materials are valid, practical and able to help students develop character in their daily lives. The implementation of the learning process becomes more meaningful because learning with character-based teaching materials can support students' understanding of the material. It is concluded that this teaching material has been valid, practical, and effective in developing the character of students.